A Comparative Analysis on Subsidy Policies of China's Public Housing Programmes: Evidence Based on Micro Surveys in Baoji - Yuan, Nannan (Journal of Reviews on Global Economics, 2014)
To understand the effects of the public housing programme and measure the feasibility of subsidy policies, this study conducts a comparative analysis on the wealth effects of two of the main subsidy policies which are the sell-oriented policy1 (SOP) and rent-oriented policy2 (ROP), implemented in the city of Baoji, China. The data in this study come from a survey conducted in 2010 in Baoji. We apply a Cobb-Douglas utility function to measure the extra benefits for households that fall under the SOP and households that fall under the ROP. Our results indicate that the low-income SOP households have a stronger taste in terms of housing consumption, and although both policies offer benefits to households, ROP households benefit more than SOP households do. The main policy conclusions drawn from our findings are that the ROP should be adopted first, and restricting resale by the purchasers is the key to achieve policy efficiency.